Congenital Heart Diseases: Risk Factors and Ultrasound Diagnostic Potential at the First Screening - A. V. Pomortsev; M. N. Karakhalis; S. A. Matulevich; G. A. Daschyan; A. A. Khalafyan; A. N. Sencha (Инновационная медицина Кубани)
Introduction: Due to the high incidence of congenital heart diseases (CHD) it is important to identify risk factors for abnormal organogenesis. There is a crucial medical need to understand cardiogenesis and possible markers of abnormalities in fetuses.Objective: To determine risk factors for CHD in pregnant women and their partners and assess CHD markers on the first ultrasound screening.Materials and methods: We analyzed 221 medical records of pregnant women with prenatally diagnosed fetal CHD and divided the patients into 2 groups: group I (n = 177) with CHD compatible with postnatal development and group II (n = 44) with CHD incompatible with postanatal development. We evaluated physical findings and somatic and reproductive history in both groups. We retrospectively analyzed 2272 ultrasound scans and first screening markers: nuchal translucency (NT) thickness and ductus venosus pulsatility index (DVPI).Results: We identified possible risk factors for fetal CHD: body mass index, P = .000; age of menarche, P = .037; chronic tonsillitis, Р = .046; cervical erosion, Р = .045; vulvovaginal candidiasis, Р = .005; vaginitis, Р = .027; cervicitis, Р = .027; chronic hepatitis B and C viruses, Р = .005; respiratory tract infection with fever during the current pregnancy, Р = .012. We built 500 networks with the highest performance for a predictive model and found that the model’s predictors did not fully represent the risk factors for CHD. CHD with increased NT thickness (≥2.5 mm) was detected in 2.24% of cases. NT thickness and DVPI were 3.37 ± 0.92 mm and 1.098 ± 0.158, respectively. According to our correlation analysis, increased DVPI and NT thickness were associated with CHD (R = 0.510).Conclusions: It is not possible to identify risk factors for CHD in fetuses by medical history, reproductive history and physical status of pregnant women, and unhealthy habits of their sexual partners. Increased NT thickness and DVPI moderately correlate with CHD incidence.